Economic policy uncertainty and corporate leverage - does cash holdings matter? Evidence from the U.S. - Zahid Jumah; Zahid Irshad Younas; Nabeel Safdar; Mamdouh Abdulaziz Saleh Al-Faryan (Cogent Economics & Finance, 2023)
This research study examines the mediating role of cash holdings between the economic policy uncertainty (EPU) and corporate leverage relationship. Using stepwise regression analysis and annual firm-level data of 2,534 U.S. firms listed at NYSE over 1995-2018, we provide novel evidence that cash holdings significantly and partially mediate the EPU-leverage relationship, accounting for a 10.72% increase in the corporate leverage during EPU. We discover that the mediating role of cash holdings between EPU and leverage is sensitive to firm-level heterogeneity. Also, the mediating effect of cash holdings remains significant based on long- and short-term leverage. Finally, our findings are robust to outliers' effect, alternate EPU measurement, endogeneity concerns and sample-selection bias. The findings of this study highlighted the role of firm cash holdings in a firm's leverage decision during economic uncertainty and recommends increasing debt financing to incentivize value-increasing decisions and mitigate agency problems by reducing the cost of free cash flows. Policymakers should be aware of public and private firms' challenges during high EPU. As we showed in this study, firms have to adjust their financial decisions during high economic uncertainty. Also, the study suggests that policymakers should maintain economic policies to avoid external shocks that may force firms to adjust their financial decision-making.
Keywords: G18; G32; G38; 330; cash holdings; Economic policy uncertainty; leverage; stepwise regression analysis